A meta-alkylthio-phenyl chain–substituted small-molecule donor as the third component for high-efficiency organic solar cells. Issue 42 (19th October 2022) - Zhang, Chenyang; Li, Jing; Ji, Lei; Hu, Hanlin; Li, Gang; Wang, Kai
Abstract : A novel small-molecule donor was designed and synthesized with appropriate energy level, complementary absorption and good compatibility with PM6. Ternary OSCs based on PM6 : Y6 system achieve PCE of 17.32%, and 18.41% for PM6 : L8-BO system. Abstract : Ternary organic solar cells (OSCs) have attracted increasing attention because they are a feasible and efficient strategy to improve the power conversion efficiency (PCE) of OSCs. However, the rational molecular design of guest materials with a suitable absorption spectrum, energy level and molecular packing is still challenging. Herein, a large-bandgap small-molecule (SM) donor, BTC, incorporated with meta -alkylthio-phenyl-substituted benzo[1, 2- b : 4, 5- b ′]dithiophene (BDT) as the core, was designed and synthesized for high-performance ternary OSCs. It possesses a deeper HOMO (highest occupied molecular orbital) level compared to PM6, which leads to a higher open-circuit voltage ( V OC ). Moreover, BTC exhibits good miscibility and complementary absorption with PM6 in the near-ultraviolet region, favoring the photovoltaic performance of OSCs by enhancing the short-circuit current density ( J SC ). Additionally, the ternary blend film with 15 wt% BTC achieved an optimized morphology with a nanofibrous network and strong face-on molecular stack, resulting in higher and more balanced charge mobilities, lower charge recombination and more efficient exciton dissociation compared to the binary blend. Therefore, we have successfully demonstrated a PCE of 17.32% for the ternary OSCs with 15 wt% BTC, with simultaneously improved V OC, J SC and FF compared to the PM6 : Y6 binary OSCs (15.51%). Moreover, the replacement of the acceptor with L8-BO further improves the PCE of ternary OSCs by up to 18.41%. This study provides a promising building block and effective design to fulfill the prerequisites of the absorption spectrum, molecular packing, energetics, and miscibility of small-molecule donors to achieve high-performance ternary OSCs.